Reconceptualizing Urban Tourism Decision Making: City Image as a Mediating Mechanism Linking Branding, e-WOM, and Tourism Entrepreneurship - Ferry Satria; Haryadi Haryadi; Syahmardi Yacob; Junaidi Junaidi (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to examine how city branding, electronic word of mouth (e-WOM), and tourism entrepreneurship influence tourists’ visiting decisions, with city image positioned as a mediating mechanism in an emerging urban tourism destination. The research was conducted in Sungai Penuh City, Indonesia, using a quantitative cross-sectional survey design. Data were collected from 200 tourists who had previously visited the city through structured questionnaires measured on a five-point Likert scale. The analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS software to test both direct and indirect relationships among constructs. The findings reveal that city branding, e-WOM, and tourism entrepreneurship have significant positive effects on city image. City image, in turn, exerts a strong and significant influence on tourists’ visiting decisions. However, the direct effects of city branding, e-WOM, and tourism entrepreneurship on visiting decisions are not statistically significant. Mediation analysis confirms that city image fully mediates the relationships between all antecedent variables and tourists’ visiting decisions. Tourists’ visiting decisions in urban destinations are primarily driven by perception-based mechanisms. Branding strategies, digital narratives, and entrepreneurial signals influence behavior only through the formation of a favourable city image. This study is limited by its cross-sectional design and focus on a single emerging city, which may constrain generalizability. This study contributes to destination marketing and urban tourism literature by integrating tourism entrepreneurship into destination image theory and highlighting the central mediating role of city image in shaping tourist decision making, offering practical insights for destination managers and policymakers.